The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13287-015-0273-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining regenerative medicine strategies to provide durable reconstructive options: auricular cartilage tissue engineering

Abstract: Recent advances in regenerative medicine place us in a unique position to improve the quality of engineered tissue. We use auricular cartilage as an exemplar to illustrate how the use of tissue-specific adult stem cells, assembly through additive manufacturing and improved understanding of postnatal tissue maturation will allow us to more accurately replicate native tissue anisotropy. This review highlights the limitations of autologous auricular reconstruction, including donor site morbidity, technical consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 127 publications
0
72
0
1
Order By: Relevance
“…Nevertheless, the usage of MSCs for cartilage engineering harbors the risk of terminal differentiation of cells and subsequent calcification and ossification of tissues (Williams et al, 2010). This results in calcification of the extracellular matrix (Gawlitta et al, 2010) -a phenomenon that is also observed in the costal cartilage framework implanted during auricular reconstruction surgerycausing an increasingly rigid construct (Jessop et al, 2016). This is an unfavorable outcome for engineered auricular tissue structures as elasticity is one of the key features of the external ear (Nimeskern et al, 2015b;Pappa et al, 2013;Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the usage of MSCs for cartilage engineering harbors the risk of terminal differentiation of cells and subsequent calcification and ossification of tissues (Williams et al, 2010). This results in calcification of the extracellular matrix (Gawlitta et al, 2010) -a phenomenon that is also observed in the costal cartilage framework implanted during auricular reconstruction surgerycausing an increasingly rigid construct (Jessop et al, 2016). This is an unfavorable outcome for engineered auricular tissue structures as elasticity is one of the key features of the external ear (Nimeskern et al, 2015b;Pappa et al, 2013;Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One common problem with cartilage tissue engineering is calcification of the neo-tissue (Jessop et al, 2016). Primary chondrocytes may terminally differentiate and become hypertrophic, which can lead to calcification and eventually ossification of the neo-tissue (Gerstenfeld and Shapiro, 1996;Phull et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The auricle is an important identifying feature of human face, and hence its deformity has a profound effect on self-confidence and psychological development in the afflicted children. Current cosmetic procedures of treating microtia mainly include the wear of auricular prosthesis, implantation of non-absorbable auricular frame materials or an autologous rib cartilage framework ( Bly et al, 2016 , Jessop et al, 2016 , Wiggenhauser et al, 2017 ). Non-absorbable frames, such as silastic or high-density polyethylene (Medpor®), generate an excellent ear shape without donor site morbidity, but they lack bioactivity and can lead to extrusion and infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical application of these technologies remains unreported due to a number of technical issues that need to be addressed, including the lack of proper cell source, the difficulty to generate ear-shaped cartilage with pre-designed 3D structure, the insufficient mechanical properties for shape maintenance, and the unfavorable host response to the engineered graft after its transplantation in vivo , etc. ( Haisch, 2010 , Jessop et al, 2016 , Nayyer et al, 2012 ). To date, the only successful clinical reports of auricular reconstruction with regenerated cartilage have utilized a two-step scaffold-free approach, in which MCs were injected subcutaneously into the lower abdomen, and the regenerated cartilage was further hand-carved into an ear-shaped framework and re-implanted into the final position ( Yanaga et al, 2009 , Yanaga et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…3D bioprinting also brings together the three parameters necessary for tissue regeneration. Compared to electrospinning, 3D bioprinting can reproduce structure and shape of tissues identical to those found in vivo [ 174 ]. This technique works in a layer-by-layer fashion, in which cells and growth factors can be included, allowing the control of the entire architecture of the tissues to be reproduced.…”
Section: 3d Regeneration Of Tmjmentioning
confidence: 99%